Substrate marking by an invasive ladybeetle: seasonal changes in hydrocarbon composition and behavioral responses. - Delphine Durieux (Public Library of Science (PLoS), 2013)
The multicolored Asian ladybeetle, Harmonia axyridis (Pallas), aggregates inside dwellings during the winter to survive the cold. Recent published reports have highlighted that overwintering individuals use hydrocarbon markings deposited on surfaces by conspecifics to orient toward aggregation sites. In the current study, monthly GC-MS analyses revealed seasonal modifications in the chemical profile of substrate markings deposited by moving individuals. The markings of overwintering ladybeetles contained larger proportions of heptacosadiene, nonacosadiene, hentriacontadienes, and methyl-nonacosanes, along with a lower proportion of heptacosene and nonacosene. This finding suggests the importance of the unsaturated and/or branched hydrocarbons in the H. axyridis aggregation process. Subsequently, we conducted behavioral assays to test whether (1) there is seasonal variation in the behavioral response of H. axyridis individuals toward substrate markings deposited by conspecifics in the same physiological state and (2) the observed behavioral modification is due to a change in ladybeetle sensitivity and/or a change in the chemical composition of the substrate marking. The results indicate that overwintering individuals exhibit a stronger "following" response toward conspecific substrate markings. This behavior is linked to both the physiological state of ladybeetles and the specific chemical profile of the marking biomolecules deposited under overwintering conditions.